2016
DOI: 10.1007/s40093-016-0140-8
|View full text |Cite
|
Sign up to set email alerts
|

Vermiconversion of biogas plant slurry and parthenium weed mixture to manure

Abstract: Purpose Parthenium hysterophorus is one among the most troublesome weeds at the global level. It is mainly controlled by chemical methods. The scientific community is in search of new but non-destructive approaches for its management. Vermicomposting is one among the promising technologies for the management of organic fraction of solid wastes. This study was undertaken to assess the vermicomposting of parthenium weed mixed with biogas plant slurry under laboratory conditions. Method Six different combinations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…The present results are in line with the findings of Ferdous, Datta, and Anwar (2017, 2018), Sarker et al (2010, Garg (2016), andHaque et al (2018), who also reported better yields of field and vegetable crops with the application of organic fertilizer. The combined application of organic manure and chemical fertilizer help improve N use efficiency through increased nutrient concentrations, soil organic matter content, water-holding capacity, bulk density, and soil temperature (Akanbi et al 2010).…”
Section: Economic Performancesupporting
confidence: 93%
See 1 more Smart Citation
“…The present results are in line with the findings of Ferdous, Datta, and Anwar (2017, 2018), Sarker et al (2010, Garg (2016), andHaque et al (2018), who also reported better yields of field and vegetable crops with the application of organic fertilizer. The combined application of organic manure and chemical fertilizer help improve N use efficiency through increased nutrient concentrations, soil organic matter content, water-holding capacity, bulk density, and soil temperature (Akanbi et al 2010).…”
Section: Economic Performancesupporting
confidence: 93%
“…Application of organic manures has been reported to increase crop yield and improve soil quality, especially soil organic matter content (Garg et al, 2005;Islam et al, 2010). Although synthetic fertilizer contains higher quantities of plant nutrients than organic fertilizer, the presence of growth-promoting agents in organic fertilizer makes them important for enhancement of soil fertility and productivity (Sanwal et al, 2007;Yadav and Garg, 2016). Soil productivity is affected by cropping systems and crop management practices including tillage, synthetic fertilizer, and organic manure management as well as enhance the causes of pesticide residues in the products (Anwar et al, 2017;Bhushan and Sharma, 2002;Islam et al, 2015b,c;Yeasmin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The quality of raw materials determines the physico-chemical characteristics of vermicompost. The results show that vermicompost can be introduced as a technology to convert organic waste into value-added products (Yadav and Garg 2016).…”
Section: Digestate Quality Testingmentioning
confidence: 95%
“…After 50-55 days it converted into vermicompost Found CN ratio 18, significantly higher phosphorus percent in slurry method, slight more K percent compare to conventional method [28], not much difference in N content are reported [29]. Almost two-fold increase in bacteria fungi and azotobacter population are recorded as compare to conventional [30]. More numbers of azosprilium and Actinomycetes recorded compare to former method [31].…”
Section: Slurry Methods (Non-enriched)mentioning
confidence: 99%